A cyber-physical production monitoring service system for energy-aware collaborative production monitoring in a smart shop floor. (15th May 2021) - Ding, Kai; Zhang, Yijie; Chan, Felix T.S.; Zhang, Chaoyang; Lv, Jingxiang; Liu, Qiang; Leng, Jiewu; Fu, Hailing
Abstract: To satisfy the varied requirements of customers and improve their sense of participation, manufacturers collaborate with equipment providers and customers to produce customer-centered individualized products. This can be achieved with the aid of new information technologies such as Cyber-Physical System (CPS) and advanced business models such as Product-Service System (PSS). However, how to incorporate CPS and PSS into the shop floor-level production system to support service-oriented collaborative manufacturing operations such as production monitoring is a vital issue. This work proposes a Cyber-Physical Production Monitoring Service System (CPPMSS) for the collaborative production monitoring of individualized product orders. First, the business model, framework, and operating logic of CPPMSS are researched. Second, the energy-aware production monitoring service for customers, manufacturers, and equipment providers in the CPPMSS is clarified. Third, a demonstrative case is studied to verify the feasibility of CPPMSS. The results show that CPPMSS can satisfy the collaborative manufacturing operations among different stakeholders in the mass individualization environment.